The influence relationship of the workplace environments satisfaction and job performance in Perbadanan Memajukan Iktisad Negeri Terengganu (PMINT) / Nur Hanees Nabilah Mohd Kamaruddin - Mohd Kamaruddin, Nur Hanees Nabilah (Faculty of Business and Management, 2017)
The purpose of this study is to measure the factors of workplace environment among employees and investigate whether there is a relationship between workplace environment and employees' job performance in Perbadanan Memajukan Iktisad Negeri Terengganu (PMINT). This research is descriptive and correlational research. This research is conducted among the officers in all departments in this organization. The total population of this study is about 50 of employees and all of them took part in this investigation. The questionnaires were distributed by hand to all respondents and they were given ample time to answer the questions. The findings show the factors of work environment and the level of employees' job performances are high. Then the most significant factor that affects workplace environment is spatial arrangement and the least significant factor that affects employees' job performance is furniture. Meanwhile, for the employees' job performance, the highest employees focused on the positive aspect of a work situation instead on negative then the least significant when fewer employees who agreed that they will work faster. The organization should try as much as possible to build a work environment that helps them to perform their job. Besides that, the organization should ensure the workplace environment is comfortable enough to support performance. Employees also must given the motivation with the environment surrounding for ensure their outcomes increased. For future research, a study of comparison about the strength between each measurement tools to measure to workplace environment factors is proposed.